Massive surgical emphysema secondary to iatrogenic tracheal laceration. (6th March 2015) - Chamberlain, Sarah; Rahman, Habib; Frunza, Gabriela; Wickham, Alexander
Abstract : A 78-year-old woman was admitted for a revision total hip replacement following a failed dynamic hip screw placed emergently 4 months earlier. Anaesthetic management consisted of general anaesthesia with endotracheal intubation and femoral nerve block. The patient's perioperative course was unremarkable except for a promptly recognised and corrected oesophageal intubation and a short period of breathing against a closed adjustable pressure limiting valve. In recovery, following a period of hypotension resistant to fluid therapy, she suddenly desaturated, developed severe facial and upper thoracic subcutaneous emphysema and type 2 respiratory failure. She was diagnosed with bilateral pneumothoraces, pneumomediastinum, pneumopericardium and surgical emphysema. This was treated emergently with supplemental oxygen and bilateral chest drains. A CT scan demonstrated a tracheal laceration, which was managed conservatively in the critical care unit. The patient had a tracheostomy on day 5 to treat an on-going air leak and later made a full recovery.